Biodiversity conservation problems and their implication on rangeland and ecotourism management in Gashaka-Gumti national park, Nigeria (2018)
The study investigates the prevalence of conservation and management problems affecting biodiversity and their implications on rangeland productivity and ecotourism activities in Gashaka-Gumti National Park, Taraba State, Nigeria. Data were collected from villagers in support zone communities and staff of the park through questionnaires. The study revealed that farming on parkland, logging, Livestock grazing and poaching are the major problems affecting biodiversity in the park. More so, lack of manpower, insufficient funding and insecurity are the major management problems identified. Implication of these on rangeland productivity and ecotourism activities of the park was downward trend in range condition, low level of tourist inflow and revenue generated by the park as well as low benefit accruable to the local economy. To reduce the spate of illegal activities and its effects, it was suggested that, community participation, conservation awareness aimed at changing local people’s attitude and provision of incentives should be embarked upon by the management of the park and government.